Tokovi robe između Grčke i zemalja zapadne Evrope - Mirko Čičak; Marica Mirić (Promet - Traffic&Transportation, 1970)
This paper deals with the freight flows proceeding between Greece and West European countries and then discusses their projections. The share of individual transport aspects is committed to an analysis to cover road, rail and sea transport. The trends evident in individual transport aspects are also reviewed as completed via Yugoslavia over the past 28 years. The authors review the measures taken by some West European countries in relation to transit traffic and define the basic trends of the traffic policy of Yugoslavia.